3D postproduction stereoscopic workflows and techniques - Baumgartner, Rick (Focal Press, Taylor & Francis Group, 2014)
"Master the complex realities of 3D postproduction workflows and solutions with this one-of-a-kind guide. Brimming with techniques that have been used on actual 3D productions and can easily be incorporated into your own workflows, Rick Baumgartner's 3D Postproduction offers you: - The best practices for 3D preproduction and production to ensure a smooth post process, saving both time and money - Abundant workflow diagrams, screen grabs, and checklists to reinforce your learning with visual cues - Common postproduction considerations such as dailies, assembly, cutting, color correction, and how they differ between 3D and 2D post pipelines - Examples of 3D gone bad and how those scenarios can be avoided - In-depth interviews with working professionals and extensive tutorials that provide practical insight from the trenches of real-world 3D postproduction - A companion website (www.focalpress.com/cw/baumgartner) with video examples of techniques described in the book and project files for you to work with An effective 3D postpostproduction workflow allows for easier and more flexible editing, greater capacity for visual effects enhancement, the ability to fix production mistakes, and much more. You can't afford to miss out! Bring your 3D projects to the next level with 3D Postproduction: Stereoscopic Workflows and Techniques"--